Test–retest reliability of pain extent and pain location using a novel method for pain drawing analysis. (6th January 2015) - Barbero, M.; Moresi, F.; Leoni, D.; Gatti, R.; Egloff, M.; Falla, D.
Abstract Background Pain drawings (PDs) are an important component of the assessment of a patient with pain. The aim of this work is to present the test–retest reliability of a novel method of quantifying the extent and location of pain. Additionally, the association between PD variables and clinical features in patients with chronic neck pain (CNP) and chronic low back pain (CLBP) was explored. Methods Fifty‐one patients with CLBP and 56 patients with CNP participated. Each patient shaded two consecutive PDs using a digital tablet. Software was developed to quantify the pain extent, to analyse the pain overlap between PDs and to produce pain frequency maps. Correlations were obtained between pain extent and clinical features including the level of pain intensity, disability, and psychological distress and cognitive function. Results The intraclass correlation coefficients for pain extent in CLBP and CNP were very high: 0.97 (95% CI: 0.95–0.98) and 0.92 (95% CI: 0.87–0.98), respectively. The Bland Altman showed a mean difference close to zero: 5.4% pixels in CNP group and 3% pixels in the CLBP group. Significant correlations were observed between pain extent and pain intensity in CLBP and CNP and pain extent and disability in CNP. There was no relation between pain extent and the level of distress or cognitive function. Conclusions A novel method for the acquisition of PD was presented. Test–retest reliability of reporting pain extent and pain location was supported in people with CNP and CLBP. Future research is needed to establish psychometric properties of PD.